Assessing the accuracy of magnetic resonance imaging in identifying early rectal cancers suitable for endoscopic intermuscular dissection - van der Schee, Lisa; Carten, Rachel; Albers, Sander C.; van den Bergh, Janneke; Braat, Manon N. G. J. A.; Goede, Arnold C.; Kol, Sabrine; Lacle, Miangela M.; Mearadji, Banafsche; Moos, Shira I.; Nota, Irene M.; Peters, Nicky H. G. M.; Prince, Jip F.; Reimerink, Jorik J.; Fariña Sarasqueta, Arantza; van Vooren, Jeanette; van Waesberghe, Jan Hein T. M.; Bastiaansen, Barbara A. J.; Vleggaar, Frank P.; Moons, Leon M. G.; Horsthuis, Karin; Brown, Gina (Endoscopy, 2025)
Selection of rectal cancers suitable for endoscopic intermuscular dissection (EID) is challenging. We aimed to evaluate whether identification of ≥1 mm of preserved muscularis propria on magnetic resonance imaging (MRI), using a systematic reporting tool (mrSRT), can identify rectal cancers suitable for EID.An expert radiologist trained 12 study radiologists in the use of the mrSRT. The radiologists then assessed a retrospective series of MRIs from 269 consecutive patients with suspected deep submucosal invasive rectal cancer. The primary objective was to determine the diagnostic accuracy of ≥1 mm of preserved muscularis propria on MRI for selecting cases that can be resected with clear margins using EID (invasion limited to the circular muscularis propria [≤pT2circ]). Diagnostic accuracy was calculated for the expert radiologist, study radiologists, and a consensus diagnosis.After applying the inclusion and exclusion criteria, 244 patient scans were included in the analysis. Histological classification confirmed 18 lesions (7.4%) were noninvasive, 109 (44.7%) were pT1, 56 (23.0%) were pT2circ, 21 (8.6%) were pT2long, 39 (16.0%) were pT3, and 1 (0.4%) was pT4. The overall diagnostic accuracy of ≥1 mm of preserved muscularis propria as a criterion for selection was 80.7% (95%CI 75.2–85.5) for the expert radiologist, 77.5% (95%CI 71.7–82.5) for the trained study radiologists, and 81.6% (95%CI 76.1–86.2) for a consensus diagnosis.Use of mrSRT to identify ≥1 mm of preserved muscularis propria on MRI allowed radiologists to assist in appropriate case selection for EID.